Mathematical modeling of hepatitis c virus (HCV) prevention among people who inject drugs: A review of the literature and insights for elimination strategies. (21st November 2019) - Pitcher, Ashley B; Borquez, Annick; Skaathun, Britt; Martin, Natasha K
Highlights: Governments seek guidance on how to achieve the World Health Organization hepatitis C virus (HCV) incidence elimination target. People who inject drugs (PWID) are a key risk group for HCV transmission. Modeling can inform what intervention scale-up is required to achieve the WHO target of 80% incidence reduction by 2030. Modeling indicates harm reduction alone is unlikely to achieve elimination targets among PWID. Existing levels of testing and treatment are insufficient to achieve WHO elimination. Models find that modest levels of HCV treatment, particularly combined with harm-reduction, can achieve elimination. Models indicate network-based and prison-based prevention strategies could provide additional population benefits. Abstract: In 2016, the World Health Organization issued global elimination targets for hepatitis C virus (HCV), including an 80% reduction in HCV incidence by 2030. The vast majority of new HCV infections occur among people who inject drugs (PWID), and as such elimination strategies require particular focus on this population. As governments urgently require guidance on how to achieve elimination among PWID, mathematical modeling can provide critical information on the level and targeting of intervention are required. In this paper we review the epidemic modeling literature on HCV transmission and prevention among PWID, highlight main differences in mathematical formulation, and discuss key insights provided by these models in terms of achieving WHO elimination targets among PWID. Overall, the vast majority of modeling studies utilized a deterministic compartmental susceptible-infected-susceptible structure, with select studies utilizing individual-based network transmission models. In general, these studies found that harm reduction alone is unlikely to achieve elimination targets among PWID. However, modeling indicates elimination is achievable in a wide variety of epidemic settings with harm reduction scale-up combined with modest levels of HCV treatment for PWID. Unfortunately, current levels of testing and treatment are generally insufficient to achieve elimination in most settings, and require further scale-up. Additionally, network-based treatment strategies as well as prison-based treatment and harm reduction provision could provide important additional population benefits. Overall, epidemic modeling has and continues to play a critical role in informing HCV elimination strategies worldwide.